A pair of non-optimal codons are necessary for the correct biosynthesis of the Aspergillus nidulans urea transporter, UreA - Manuel Sanguinetti; Andrés Iriarte; Sotiris Amillis; Mónica Marín; Héctor Musto; Ana Ramón (Royal Society Open Science, 2019)
In both prokaryotic and eukaryotic genomes, synonymous codons are unevenly used. Such differential usage of optimal or non-optimal codons has been suggested to play a role in the control of translation initiation and elongation, as well as at the level of transcription and mRNA stability. In the case of membrane proteins, codon usage has been proposed to assist in the establishment of a pause necessary for the correct targeting of the nascent chains to the translocon. By using as a model UreA, the Aspergillus nidulans urea transporter, we revealed that a pair of non-optimal codons encoding amino acids situated at the boundary between the N-terminus and the first transmembrane segment are necessary for proper biogenesis of the protein at 37°C. These codons presumably regulate the translation rate in a previously undescribed fashion, possibly contributing to the correct interaction of ureA-translating ribosome-nascent chain complexes with the signal recognition particle and/or other factors, while the polypeptide has not yet emerged from the ribosomal tunnel. Our results suggest that the presence of the pair of non-optimal codons would not be functionally important in all cellular conditions. Whether this mechanism would affect other proteins remains to be determined.